Model Matematika Penanggulangan Pencemaran Udara dengan Penanaman Pohon - Esty Wahyuni; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2018)
Abstract – Air pollution is greatly feared by urban communities, as the majority of them use motor vehicles. The purpose of the research is to know the factors that increas air pollution using mathematical model. This research is a basic research using descriptive method. Research steps are identifying problems, determining variables, parameters, assumptions, forming mathematical models, analyzing models and interpreting models. The mathematical model analysis results obtained by a stable fixed point. Where the fixed point is which is the maximum value of each concentration. The stability behavior of the fixed point is strongly influenced by the condition of the parameter value of the model that is the rate of change of each factor. Factors that affect the increase of carbon monoxide in the air are the sources of carbon monoxide derived from motor vehicles, the source must be controlled so that the increase of carbon monoxide in the air can be limited.